KRAS mutations in blood circulating cell-free DNA: a pancreatic cancer case-control - Le Calvez-Kelm, Florence; Foll, Matthieu; Wozniak, Magdalena B; Delhomme, Tiffany M; Durand, Geoffroy; Chopard, Priscilia; Pertesi, Maroulio; Fabianova, Eleonora; Adamcakova, Zora; Holcatova, Ivana; Foretova, Lenka; Janout, Vladimir; et al. (Oncotarget, 2016)
The utility of KRAS mutations in plasma circulating cell-free DNA (cfDNA) samples as non-invasive biomarkers for the detection of pancreatic cancer has never been evaluated in a large case-control series. We applied a KRAS amplicon-based deep sequencing strategy combined with analytical pipeline specifically designed for the detection of low-abundance mutations to screen plasma samples of 437 pancreatic cancer cases, 141 chronic pancreatitis subjects, and 394 healthy controls. We detected mutations in 21.1% (N=92) of cases, of whom 82 (89.1%) carried at least one mutation at hotspot codons 12, 13 or 61, with mutant allelic fractions from 0.08% to 79%. Advanced stages were associated with an increased proportion of detection, with KRAS cfDNA mutations detected in 10.3%, 17,5% and 33.3% of cases with local, regional and systemic stages, respectively. We also detected KRAS cfDNA mutations in 3.7% (N=14) of healthy controls and in 4.3% (N=6) of subjects with chronic pancreatitis, but at significantly lower allelic fractions than in cases. Combining cfDNA KRAS mutations and CA19-9 plasma levels on a limited set of case-control samples did not improve the overall performance of the biomarkers as compared to CA19-9 alone. Whether the limited sensitivity and specificity observed in our series of KRAS mutations in plasma cfDNA as biomarkers for pancreatic cancer detection are attributable to methodological limitations or to the biology of cfDNA should be further assessed in large case-control series.
Keywords: mutace; Proto-Oncogene Proteins p21(ras); Female; Phenotype; antigen CA-19-9; ženské pohlaví; duktální karcinom slinivky břišní; mutační analýza DNA; Predictive Value of Tests; Reproducibility of Results; Pancreatic Neoplasms; prediktivní hodnota testů; Slovakia; Gene Frequency; lidé; staging nádorů; Pilot Projects; nádory slinivky břišní; DNA Mutational Analysis; Mutation; genetická predispozice k nemoci; pilotní projekty; studie případů a kontrol; Genetic Predisposition to Disease; frekvence genu; cirkulující nádorová DNA; reprodukovatelnost výsledků; Male; nádorové biomarkery; Aged; Case-Control Studies; Czech Republic; Circulating Tumor DNA; Carcinoma, Pancreatic Ductal; Česká republika; CA-19-9 Antigen; Biomarkers, Tumor; lidé středního věku; Slovenská republika; senioři; mužské pohlaví; fenotyp; protoonkogenní proteiny p21(ras); Middle Aged; Neoplasm Staging; Humans